2019
DOI: 10.1002/cptc.201800227
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐Substituted Tetraphenylethene Isomers with Different Triboluminescence Properties

Abstract: Three isomers of fluorine‐substituted tetraphenylethenes (TPE) demonstrate totally different triboluminescence (TL) properties resulting from minor structural differences. Studying the photophysical properties, packing models, and the single‐crystal structure combined with density functional theory (DFT) calculations confirmed that bright TL emission can be attributed to the high emission intensity, strongintermolecular interactions and large dipole moments in the solid state, indicating that the introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
(12 reference statements)
0
11
0
2
Order By: Relevance
“…For piezoelectric crystals, the accumulation of charges on the cracked surface creates a strong electric field to excite the light. [31][32][33][34] Based on these results, it can be found that among the affecting factors, the piezoelectric effect originating from the non-centrosymmetric space group plays a more positive role for ML. Besides, the stuck packing mode plays an important role in achieving ML properties.…”
Section: The Relationship Between Packing Mode and MLmentioning
confidence: 92%
“…For piezoelectric crystals, the accumulation of charges on the cracked surface creates a strong electric field to excite the light. [31][32][33][34] Based on these results, it can be found that among the affecting factors, the piezoelectric effect originating from the non-centrosymmetric space group plays a more positive role for ML. Besides, the stuck packing mode plays an important role in achieving ML properties.…”
Section: The Relationship Between Packing Mode and MLmentioning
confidence: 92%
“…studied crystals of the previous reportedlyf luorine-and methoxy-substituted TPE, (Z)-/(E)-TPE-FM ( Figure 15 a). [78] When ac rystal of (E)-TPE-FMw as sheared by using glass or as patula, no TL waso bserved.H owever,( Z)-TPE-FM exhibited ab right blue TL emission under the same operation, even in daylight ( Figure 15 b). The TL of (Z)-TPE-FMh ad ap eak maximum at l = 425 nm, which nicely corresponded to the PL in the as-prepared state (Figure 15 c).…”
Section: Mechanoluminescence Propertiesoft He Z/e Isomersmentioning
confidence: 96%
“…Recently, Tu et al. studied crystals of the previous reportedly fluorine‐ and methoxy‐substituted TPE, ( Z )‐/( E )‐TPE‐FM (Figure a) . When a crystal of ( E )‐TPE‐FM was sheared by using glass or a spatula, no TL was observed.…”
Section: Mechanoluminescence Properties Of the Z/e Isomersmentioning
confidence: 99%
“…扭曲构型的分子间相互作用和抑制分子间π … π堆积 有助于构建高亮度力致发光材料, 四(三)苯乙烯(TPE) 由于其特殊的扭曲构型被广泛应用于力致发光材料领 域 [46][47][48][49][50][51][52][53][54] . 为了研究分子排列对力致发光的影响, Li 等报 道了一系列具有力致发光性质的有机小分子化合物, 对 分子结构-排列-性能进行了系统、深入的研究.…”
Section: 分子排列对力致发光的影响unclassified
“…同时, 他们还通过改变 TMPE 分子上烷基链的长度调控分子排列, 当烷基链增 长时, 分子 TBPE 和 THPE 的排列变得疏松, 分子间相 互作用减弱, 无 ML 现象产生. 另外, 他们还报道了一 种纯碳氢 ML 材料 TETPE 和一系列基于 TPE 的同分异 构体 [47][48] , 研究结果证明, 分子间强的相互作用和紧密 的分子堆积是产生 ML 的主要原因. 该结论也在分子 mm-TPE(PI)2 和 pp-TPE(PI)2 中进一步被证实 [49] .…”
Section: 分子排列对力致发光的影响unclassified